Sphingosine 1-Phosphate Receptors and Metabolic Enzymes as Druggable Targets for Brain Diseases - Grassi, Sara; Mauri, Laura; Prioni, Simona; Cabitta, Livia; Sonnino, Sandro; Prinetti, Alessandro; Giussani, Paola (Frontiers in Pharmacology, 2019)
The central nervous system is characterized by a high content in sphingolipids, and by an high diversity in term of different structures. Stage- and cell-specific sphingolipid metabolism and expression are crucial for the brain development and maintenance along adult age. On the other hand, deep dysregulation of sphingolipid metabolism, leading to altered sphingolipid pattern, is associated with the majority of neurological and neurodegenerative diseases, even those totally lacking common etiological background. Thus, sphingolipid metabolism has always been regarded as a promising pharmacological target for the treatment of brain disorders. However, any therapeutic hypothesis applied to complex, amphipathic sphingolipids, components of cellular membranes, has so far failed, probably due to the high regional complexity and specificity of the different biological roles of these structures. On the other hand, simpler sphingosine-based lipids, including ceramide and sphingosine 1-phosphate are important regulators of brain homeostasis, and, thanks to the relative simplicity of their metabolic network, they seem a feasible druggable target for the treatment of brain diseases. The enzymes involved in the control of the levels of bioactive sphingoids, as well as the receptors engaged by these molecules, have increasingly allured pharmacologists and clinicians, and eventually fingolimod, a functional antagonist of sphingosine 1-phosphate receptors with immunomodulatory properties, was approved for the therapy of relapsing-remitting multiple sclerosis. Considering the importance of neuroinflammation in many other brain diseases, we would expect and extension of the use of such analogs for the treatment of other ailments in the future. Nevertheless, many aspects other than neuroinflammation are regulated by bioactive sphingoids in healthy brain, and dysregulated in brain disease. In this review, we are addressing the multifaceted possibility to address the metabolism and biology of bioactive sphingosine 1-phosphate as novel targets for the development of therapeutic paradigms and the discovery of new drugs.